2008
DOI: 10.1111/j.1365-2133.2008.08793.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial comparing the effectiveness of 308-nm excimer laser alone or in combination with topical hydrocortisone 17-butyrate cream in the treatment of vitiligo of the face and neck

Abstract: Recalcitrant vitiligo of the face and neck may benefit from the combination of excimer laser phototherapy with topical hydrocortisone 17-butyrate cream.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 27 publications
0
76
0
1
Order By: Relevance
“…Details regarding the trial design and main clinical results have been published elsewhere [6]. A total of 120 patients with different varieties of vitiligo (focal vs. generalized) were initially screened, and 84 underwent randomization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details regarding the trial design and main clinical results have been published elsewhere [6]. A total of 120 patients with different varieties of vitiligo (focal vs. generalized) were initially screened, and 84 underwent randomization.…”
Section: Methodsmentioning
confidence: 99%
“…In a recently completed randomized clinical trial, up to 42% of patients who were previously unresponsive to conventional treatment modalities attained a 75% or greater reduction of the lesional areas of the face and neck when treated with a 12-week course of excimer laser therapy combined with topical corticosteroids [6]. Because the treatment is time consuming and highly demanding in terms of personal commitment, a predictive model for clinical response may have the obvious advantages of helping to select likely responders and anticipating treatment duration in individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…They also revealed that combination of betamethasone dipropionate and NB-UVB resulted in the highest repigmentation rate (Lotti et al, 2008). In other study, Sassi and colleagues also showed that combination of excimer laser and topical hydrocortisone was effective in treatment of recalcitrant vitiligo of the face and neck (Sassi, 2008). …”
Section: Place Of Corticosteroids In Treatment Of Vitiligomentioning
confidence: 99%
“…Two were assessed this using DLQI 49,62 and two 407,424 used Skindex-29; however, we were not able to perform statistical analysis on these data. Percentage of repigmentation > 75%…”
Section: Quality Of Lifementioning
confidence: 99%